2022
DOI: 10.3390/ijms23169258
|View full text |Cite
|
Sign up to set email alerts
|

Aspiletrein A Induces Apoptosis Cell Death via Increasing Reactive Oxygen Species Generation and AMPK Activation in Non-Small-Cell Lung Cancer Cells

Abstract: Lung cancer remains a leading cause of death in cancer patients, and deregulation of apoptosis is a serious concern in clinical practice, even though therapeutic intervention has been greatly improved. Plants are a versatile source of biologically active compounds for anticancer drug discovery, and aspiletrein A (AA) is a steroidal saponin isolated from Aspidistra letreae that has a potent cytotoxic effect on various cancer cell lines. In this study, we investigated and determined the underlying molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Treatment with aspiletrein A led to a decrease in Bcl-2 levels and an increase in caspase 3 and PARP cleavage. The molecular mechanism was identified to be associated with elevated intracellular ROS and activation of AMPK signaling (Witayateeraporn et al, 2022). Network pharmacology analysis also revealed that STAT3 is a target of these compounds in regulating apoptosis (Iksen et al, 2023).…”
Section: Steroids and Steroidal Saponinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with aspiletrein A led to a decrease in Bcl-2 levels and an increase in caspase 3 and PARP cleavage. The molecular mechanism was identified to be associated with elevated intracellular ROS and activation of AMPK signaling (Witayateeraporn et al, 2022). Network pharmacology analysis also revealed that STAT3 is a target of these compounds in regulating apoptosis (Iksen et al, 2023).…”
Section: Steroids and Steroidal Saponinsmentioning
confidence: 99%
“…Aspiletrein A, a steroidal saponin found in Aspidistra letreae , has significant anticancer effects, particularly in lung cancer (Ho et al, 2020; Iksen et al, 2023; Nguyen et al, 2021). In vitro experiments revealed that aspiletrein A induced apoptosis in a dose‐dependent manner (Witayateeraporn et al, 2022). Treatment with aspiletrein A led to a decrease in Bcl‐2 levels and an increase in caspase 3 and PARP cleavage.…”
Section: Natural Compounds and Small Molecules Targeting Bcl‐2 Family...mentioning
confidence: 99%
“…The potential virulence of Serratia marcescens to Diaphorina citri has been known for years, while the underlying molecular mechanism remains unclear. Reactive oxygen species (ROS) mainly include the superoxide anion (O 2 − ), the hydroxyl radical (OH˙), and hydrogen peroxide (H 2 O 2 ) and play a central role in insect innate immunity by mediating immune signaling or regulating gut microbiota 27,28 . Oral ingestion of Serratia marcescens resulted in an elevation of ROS levels in the midguts of Lutzomyia longipalpis 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) mainly include the superoxide anion (O 2 − ), the hydroxyl radical (OH˙), and hydrogen peroxide (H 2 O 2 ) and play a central role in insect innate immunity by mediating immune signaling or regulating gut microbiota. 27,28 Oral ingestion of Serratia marcescens resulted in an elevation of ROS levels in the midguts of Lutzomyia longipalpis. 27 Cell apoptosis or autophagy will be induced under elevated oxidative stress.…”
Section: Introductionmentioning
confidence: 99%